Tissue engineering applied to reconstructive surgery. - Brey, E.M (IEEE Engineering in medicine and biology magazine)
Tissue engineering has the potential to change the way reconstructive surgery is practised as well as increased patient quality of life. This review illustrates a small fraction of the areas in reconstructive surgery that can benefit from tissue engineering. The authors, at the University of Texas M.D. Anderson Cancer Center, believe that the best way to bring this potential to fruition is by bringing together experts from the operating room, engineering, acedemia, and industry, and combining the abilities and knowledge of each to obtain results that could not be accomplished independently.